"Fading Beams of the Nineteenth Century:" Radicalism and Early Socialism in Canada's 1890s - Homel, Gene Howard (Labour / Le Travail, 1980)
The intensified problems of an increasingly urban and industrial Canada by the late nineteenth century stimulated the development of a significant movement of radical social critics. This article describes and interprets the convictions, supporters, and organizations of Canadian radicalism during the 1890s, encompassing labour leaders, anti-monopolists, single taxers, social gospellers, and the like. The radicals rejected free-market assumptions and, on the basis of their concern for ethical values and for the protection of the productive elements of the community, advocated a radically restructured society based on cooperation and brotherhood. The article explains the rise of socialist ideas against the background of traditional forms of radical protest.